TiO2-x (F) powder, preparation method thereof and application of TiO2-x (F) powder in strengthening performance of solid hydrogen storage material
Through the synergistic effect of the preparation of TiO2-x(F) powder and the magnesium hydride matrix, the problems of high hydrogen release temperature and slow low-temperature kinetic performance of magnesium-based solid hydrogen storage materials were solved, and the hydrogen storage performance of MgH2 was significantly improved.
Patent Information
- Application Number
- CN202311016599.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
AI Technical Summary
The high hydrogen release temperature and slow low-temperature kinetic properties of magnesium-based solid hydrogen storage materials limit their practical application.
By preparing TiO2-x(F) powder and forming active species in situ with the magnesium hydride matrix during hydrogen absorption/discharge, the electron flow is accelerated by oxygen vacancies, and the hydrogen storage performance of MgH2 is improved in concert.
The initial hydrogen release temperature of MgH2 was significantly reduced, from 416℃ to 189℃, and all hydrogen was released in just 7 minutes at 250℃. The hydrogen absorption amount reached 3wt.% within 120min at 50℃, and the circulation retention rate was as high as 93.3%.
Smart Images

Figure CN119490221A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a TiO 2-x (F) powder and its preparation method and application in enhancing the performance of solid hydrogen storage materials belong to the technical field of hydrogen storage materials and their preparation. Background Art
[0002] Compared with fossil fuels, hydrogen energy produces only water as a combustion product, which can achieve carbon-free emissions. In addition, hydrogen has an extremely high combustion calorific value, three times that of gasoline, is abundant in sources, and is safe, with significant advantages. The large-scale utilization of hydrogen energy mainly includes preparation, storage, and application. So far, hydrogen production and use technologies have developed relatively maturely, and how to store and transport hydrogen energy safely, economically, and efficiently is an important challenge currently faced. According to the physical state of hydrogen, hydrogen storage methods are mainly divided into high-pressure gaseous hydrogen storage, liquid hydrogen storage, and solid hydrogen storage. High-pressure gaseous hydrogen storage is the earliest hydrogen storage method used, but its hydrogen storage capacity per unit volume is small and has a high risk factor. Liquid hydrogen storage is divided into low-temperature liquid hydrogen storage and liquid organic hydrogen storage; low-temperature liquid hydrogen storage has a high hydrogen storage capacity per unit volume, but requires special insulated containers and is currently only used in aerospace and other fields. Liquid organic hydrogen storage is prone to disadvantages such as difficulty in controlling hydrogen purity and poor organic safety; solid-state hydrogen storage refers to hydrogen storage achieved through physical adsorption or chemical reaction with other alloy elements, and has the characteristics of good safety and high volume hydrogen storage density.
[0003] MgH2, as a light metal hydride, has significant advantages and is the most promising solid-state hydrogen storage material for large-scale application in the future. Its mass hydrogen storage density is 7.6wt.%, and its volume hydrogen storage density is 110g / L. It has excellent reversibility and can be cycled more than 1,000 times. However, the interaction between Mg-H bonds is very strong, and the enthalpy change of the hydrogen release reaction is about 75kJ / mol. It has high thermal stability and can generally be completely dehydrogenated by heating to above 350°C. In addition, the hydrogenation and dehydrogenation reactions of magnesium are very slow. Magnesium powder hardly absorbs hydrogen at 300°C and 10bar hydrogen pressure. When the temperature rises to 400°C, it still takes several hours to complete the hydrogen absorption. The high thermodynamic stability and slow kinetic performance at low temperatures limit the practical application of MgH2.
[0004] At present, the hydrogen storage performance of MgH2 is mainly modified by alloying, adding catalysts, nano-sizing, and constructing composite systems. Among them, by adding a suitable catalyst, active sites and nucleation centers can be provided for the hydrogen absorption / desorption reaction, the activation energy of the hydrogen absorption / desorption process can be reduced, and the thermal / dynamic properties of MgH2 can be further improved. Taking metal Ti as an example, Ti, as a transition metal element, has a d orbital that can interact with the antibonding orbital of hydrogen, and can generate a new metastable phase TiH2 during the hydrogen absorption and desorption process, effectively promoting the diffusion of hydrogen, and showing an excellent catalytic effect. Therefore, it is very necessary to provide a Ti-containing catalyst for further improving the thermal / dynamic properties of MgH2. Summary of the invention
[0005] The present invention aims to solve the problems of high hydrogen desorption temperature and slow low-temperature kinetics of existing magnesium-based solid hydrogen storage materials, and provides a TiO 2-x (F) Powder and preparation method thereof and application in enhancing the performance of solid-state hydrogen storage materials, specifically by TiO 2-x (F) The above problems are solved by the synergistic effect of active species formed in situ with the magnesium hydride matrix during the hydrogen absorption / desorption process and oxygen vacancies accelerating the flow of electrons.
[0006] The technical solution of the present invention:
[0007] One of the purposes of the present invention is to provide a TiO 2-x (F) A method for preparing a powder, the method comprising the following steps:
[0008] (1) TiO2(F) powder was prepared by a hydrothermal method using tetrabutyl titanate, hydrofluoric acid and anhydrous ethanol as raw materials;
[0009] (2) Calcination of TiO2(F) powder in a reducing atmosphere introduces oxygen vacancies to obtain TiO 2-x (F) Powder, wherein x<2.
[0010] It is further defined that the hydrothermal reaction temperature in (1) is 160-200°C and the reaction time is 16-20h.
[0011] It is further defined that the concentration of hydrofluoric acid in (1) is 35-45 wt.%; and the volume ratio of tetrabutyl titanate, hydrofluoric acid and anhydrous ethanol is (10-30):(5-10):(10-30).
[0012] It is further defined that the reducing atmosphere in (2) is a mixture of an inert gas and a reducing gas, the calcination temperature is 180 to 220° C., and the calcination time is 2 to 4 hours.
[0013] It is further defined that the volume ratio of the inert gas to the reducing gas in the mixed gas is (90-98):(10-2).
[0014] In a further embodiment, the inert gas is argon or helium, and the reducing gas is hydrogen.
[0015] It is further defined that the specific operation of (1) is: 20 mL of tetrabutyl titanate and 8 mL of hydrofluoric acid are mixed to form a solution A, 20 mL of anhydrous ethanol is added to the solution A to form a solution B, and then the solution B is reacted in an autoclave at 180° C. for 16 h, and after the reaction, the solution is centrifuged, washed, and dried to obtain TiO2(F) powder.
[0016] It is further defined that the concentration of hydrofluoric acid is 40 wt. %.
[0017] The second object of the present invention is to provide a catalyst for MgH2 hydrogen storage material, the catalyst comprising TiO 2-x (F) Powder.
[0018] The third object of the present invention is to provide a MgH2-TiO 2-x (F) A composite hydrogen storage material comprising the above-mentioned TiO 2-x (F) powder and MgH2 powder.
[0019] Further defined, TiO 2-x (F) The proportion of powder in the composite hydrogen storage material is (3-6)±0.5wt.%.
[0020] Further defined, TiO 2-x (F) The powder is in the form of nanosheets with a layer thickness of 3 to 6 nm; the MgH2 powder is in the form of spherical powder with a particle size of 2-15 μm.
[0021] The third object of the present invention is to provide a MgH2-TiO 2-x (F) A method for preparing a composite hydrogen storage material, comprising: 2-x (F) powder and MgH2 powder are obtained by mechanical mixing.
[0022] It is further defined that the mechanical mixing method is high-energy ball milling, and the high-energy ball milling treatment conditions are: under a protective atmosphere, the ball-to-material ratio is 20:1, intermittent ball milling is adopted, each ball milling is 30 minutes, and the rest time is 30 minutes. The total ball milling time is 2 to 5 hours, and the ball milling speed is 1600 to 1800 rpm.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention prepares a fluorinated transition metal Ti oxide additive doped with oxygen vacancies. In addition to the multivalent metal Ti being able to generate TiH2 and metal Ti as an electron transfer medium during the hydrogen absorption / desorption process, the F atoms on the surface of the transition metal Ti atoms themselves have a strong electronegativity and can also capture the electrons of Mg, generating MgF2 active catalytic species during the hydrogen absorption / desorption process, further improving the hydrogen storage performance of MgH2. At the same time, the construction of oxygen vacancies on the surface of the transition metal Ti atoms can provide active sites for the nucleation and growth of Mg / MgH2, and can greatly accelerate the flow of electrons during the hydrogen absorption / desorption process, improve thermal / dynamic performance, and achieve reversible hydrogen absorption / desorption of magnesium-based hydrogen storage materials at low temperatures.
[0025] (2) TiO prepared by the present invention 2-x (F) powder, the initial dehydrogenation temperature of commercial MgH2 powder can be reduced from 416℃ to 189℃. At 250℃, all hydrogen can be released in just 7min. At the same time, at 50℃, the hydrogen absorption within 120min is as high as 3wt.%. After ten cycles, the capacity retention rate is as high as 93.3%.
[0026] (3) The preparation process of the composite hydrogen storage material provided by the present invention is simple and mature, and the raw materials are cheap and easily available, which is convenient for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The TiO prepared in Example 1 2-x (F) Transmission electron microscopy image;
[0028] Figure 2 The TiO prepared in Example 1 2-x (F) High-resolution F1s X-ray photoelectron spectrum;
[0029] Figure 3 MgH2-TiO prepared in Example 1 2-x (F) Comparison of temperature-dependent hydrogen release curves of the MgH2-TiO2 (F) composite hydrogen storage material prepared in Comparative Example 1 and the MgH2 hydrogen storage material in Comparative Example 2;
[0030] Figure 4 MgH2-TiO prepared in Example 1 2-x (F) and the comparison diagram of the normalized isothermal hydrogen release curve of the MgH2-TiO2 (F) composite hydrogen storage material prepared in Comparative Example 1 at 250°C;
[0031] Figure 5 MgH2-TiO prepared in Example 2-x (F) is a comparison of isothermal hydrogen absorption curves of the MgH2-TiO2 (F) composite hydrogen storage material prepared in Comparative Example 1 at 100°C and a hydrogen pressure of 3.2 MPa;
[0032] Figure 6 MgH2-TiO prepared in Example 1 2-x (F) Cyclic hydrogen absorption / desorption diagram of the composite hydrogen storage material. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0036] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0037] Example 1
[0038] (1)TiO 2-x (F) Preparation of powder:
[0039] First, 20 mL of tetrabutyl titanate and 8 mL of hydrofluoric acid (concentration of 40 wt.%) were mixed, and 20 mL of anhydrous ethanol was added dropwise to the above solution. Subsequently, the mixed solution was transferred to a 100 mL autoclave and reacted at 180°C for 16 hours. After the reaction, the TiO2 (F) powder was obtained by centrifugation, washing and drying.
[0040] Then, in the Ar / H2 mixed gas (V Ar :V H2 The TiO2(F) powder was calcined at 200°C for 2 h to obtain TiO 2-x (F) Powder.
[0041] The obtained TiO 2-x (F) The powder was subjected to structural characterization, and the results were as follows Figure 1 and Figure 2 shown. Figure 1TiO 2-x (F) Transmission electron micrograph of the powder. Figure 1 It can be seen that TiO 2-x (F) The powder is in the form of ultrathin nanosheets with a layer thickness of about 5 nm. Figure 2 TiO 2-x (F) High-resolution F1s X-ray photoelectron energy map of the powder, Figure 2 It can be seen that the F ions on the TiO2 surface mostly exist in the form of Ti-F bonds, and there are a small amount of Ti-F-Ti bonds.
[0042] (2)MgH2-TiO 2-x (F) Preparation of composite hydrogen storage materials:
[0043] Under argon atmosphere, TiO 2-x (F) powder and MgH2 powder were mixed at mass fractions of 5wt.% and 95wt.% respectively. A certain amount of zirconia beads were weighed according to a ball-to-material ratio of 20:1. The beads were placed in a ball mill and subjected to high-energy ball milling at a rotation speed of 1750rpm. Intermittent ball milling was adopted, with each ball milling lasting 30min and resting for 30min. The total ball milling time was 3h.
[0044] The obtained MgH2-TiO 2-x (F) The composite hydrogen storage material is tested for hydrogen absorption / desorption performance. The results are as follows Figure 3 to Figure 6 shown. Figure 3 MgH2-TiO 2-x (F), MgH2-TiO 2-x (F) Comparison of temperature-dependent hydrogen release curves of composite hydrogen storage materials and MgH2 hydrogen storage materials. Figure 3 It can be seen that MgH2-TiO 2-x (F) The initial dehydrogenation temperature of the composite hydrogen storage material dropped to 189°C, which was about 227°C lower than that of pure MgH2, showing the most excellent dehydrogenation thermodynamic performance. Figure 4 MgH2-TiO 2-x (F) The normalized temperature-dependent hydrogen release curve of the composite hydrogen storage material at 250°C shows that the composite material can release all the hydrogen in just 7 minutes. 2-x (F) The hydrogen desorption product of the composite hydrogen storage material was subjected to a hydrogen absorption test at 100°C and a hydrogen pressure of 3.2 MPa. Figure 5 It can be seen that the amount of hydrogen absorbed by the hydrogen desorption product is as high as 3.621wt.% within 10 minutes. Figure 6 MgH2-TiO 2-x (F) Cyclic hydrogen absorption / desorption diagram of composite hydrogen storage materials, Figure 6 It can be seen that the retention rate is as high as 93.3% after 10 cycles.
[0045] Comparative Example 1
[0046] As a comparative sample, TiO2(F) powder without oxygen vacancies was prepared and the performance of MgH2-TiO2(F) composite hydrogen storage material was tested.
[0047] (1) Preparation of TiO2(F) powder:
[0048] Mix 20 mL of tetrabutyl titanate and 8 mL of hydrofluoric acid (concentration of 40 wt.%), and add 20 mL of anhydrous ethanol dropwise into the above solution. Then, transfer the mixed solution to a 100 mL autoclave and react at 180°C for 16 h. After the reaction, centrifuge, wash and dry to obtain TiO2 (F) powder.
[0049] (2) Preparation of MgH2-TiO2(F) composite hydrogen storage material:
[0050] Under argon atmosphere, TiO2(F) powder and MgH2 powder were mixed with mass fractions of 5wt.% and 95wt.% respectively. According to the ball-to-material ratio of 20:1, a certain amount of zirconia beads were weighed and placed in a ball mill. High-energy ball milling was carried out at a speed of 1750rpm. Intermittent ball milling was adopted, with each ball milling time of 30min and rest time of 30min. The total ball milling time was 3h.
[0051] The obtained MgH2-TiO2(F) composite hydrogen storage material was tested for its hydrogen absorption / desorption performance. Figure 3 The temperature-dependent hydrogen desorption curves show that the initial desorption temperature of the MgH2-TiO2(F) composite hydrogen storage material drops to 203.2℃, which is still higher than that of the MgH2-TiO 2-x (F) Composite hydrogen storage material. Figure 4 From the isothermal dehydrogenation curve, it can be seen that the MgH2-TiO2(F) composite hydrogen storage material has not been completely dehydrogenated within 10 minutes. Figure 5 The isothermal hydrogen absorption curve shows that at 100℃, the hydrogen desorption product of MgH2-TiO2(F) composite hydrogen storage material is only 3.321wt.%, slightly lower than that of MgH2-TiO2(F). 2-x (F) Composite hydrogen storage materials.
[0052] Comparative Example 2
[0053] As a comparative sample, a commercially available MgH2 hydrogen storage material was tested.
[0054] In order to evaluate the hydrogen storage performance of MgH2, variable temperature hydrogen desorption and isothermal hydrogen absorption / desorption tests were performed on commercially available MgH2. Figure 3 Analysis shows that the initial dehydrogenation temperature of commercially available MgH2 is as high as 416°C, and the total dehydrogenation amount is 7.5wt.%.2-x (F) Under the same isothermal hydrogen absorption / desorption conditions, commercially available MgH2 cannot absorb / desorb hydrogen, and the amount of hydrogen absorbed / desorbed is 0.
[0055] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A TiO 2-x (F) A method for preparing a powder, characterized in that: include: (1) TiO2(F) powder was prepared by a hydrothermal method using tetrabutyl titanate, hydrofluoric acid and anhydrous ethanol as raw materials; (2) Calcination of TiO2(F) powder in a reducing atmosphere introduces oxygen vacancies to obtain TiO 2-x (F) Powder, wherein x<2.
2. The preparation method according to claim 1, characterized in that: (1) The hydrothermal reaction temperature is 160-200° C. and the reaction time is 16-20 h; the concentration of hydrofluoric acid is 35-45 wt.%; and the volume ratio of tetrabutyl titanate, hydrofluoric acid and anhydrous ethanol is (10-30):(5-10):(10-30).
3. The preparation method according to claim 1, characterized in that: (2) The reducing atmosphere is a mixture of inert gas and reducing gas, the calcination temperature is 180-220°C, and the calcination time is 2-4 hours.
4. The preparation method according to claim 3, characterized in that: The volume ratio of the inert gas and the reducing gas in the mixed gas is (90-98):(10-2); the inert gas is argon or helium, and the reducing gas is hydrogen.
5. A catalyst for MgH2 hydrogen storage material, characterized in that: The TiO obtained by the preparation method according to any one of claims 1 to 4 2-x (F) Powder.
6. A MgH2-TiO 2-x (F) A composite hydrogen storage material, characterized in that The TiO obtained by the preparation method according to any one of claims 1 to 4 2-x (F) powder and MgH2 powder.
7. The composite hydrogen storage material according to claim 6, characterized in that: TiO 2-x (F) The proportion of powder in the composite hydrogen storage material is (3-6)±0.5wt.%.
8. The composite hydrogen storage material according to claim 6, characterized in that: TiO 2-x (F) The powder is in the form of nanosheets with a layer thickness of 3 to 6 nm; the MgH2 powder is in the form of spherical powder with a particle size of 2-15 μm.
9. MgH2-TiO according to claim 6 2-x (F) A method for preparing a composite hydrogen storage material, characterized in that: TiO 2-x (F) powder and MgH2 powder are obtained by mechanical mixing.
10. The preparation method according to claim 9, characterized in that: The mechanical mixing method is high-energy ball milling. The high-energy ball milling treatment conditions are: under a protective atmosphere, the ball-to-material ratio is 20:1, intermittent ball milling is adopted, each ball milling is 30 minutes, and the rest time is 30 minutes. The total ball milling time is 2 to 5 hours, and the ball milling speed is 1600 to 1800 rpm.
Citation Information
Cited By
Monatomic palladium-loaded titanium dioxide graded nanospheres for catalytic magnesium hydride
CN120939931A
Monatomic Nb substituted TiO2 / TiOF2 heterojunction for catalytic magnesium hydride
CN121016799A
Composite hydrogen storage material and preparation method thereof
CN121158730A